Sustainable utilization of discarded foundry sand and crushed brick masonry aggregate in the production of lightweight concrete. Issue 1 (2nd January 2017) - Mailar, Gireesh; Sujay Raghavendra, N.; Hiremath, Parameshwar; Sreedhara, B. M.; Manu, D. S.
Abstract: Nowadays, there is a considerable shortage in the availability of river sand and natural stone aggregate for the construction activities all around the globe and the way out is being worked out by the use of discarded foundry sand and crushed brick masonry aggregate for construction purposes. In the present study, river sand was partly replaced by the discarded foundry sand procured from steel moulding industries and the crushed brick masonry aggregate was used as coarse aggregate for the production of lightweight concrete. The experimental program involved casting of six distinct mixes with 0%, 20%, 40%, 60%, 80% & 100% replacement of fine aggregate by discarded foundry sand. The mechanical and durability properties of the lightweight concrete were assessed for each of the six diverse blends. Even though the 80% and 100% replacement mixes were found to be less dense than the rest of the mix, the blend of 40% replacement acquired desirable mechanical and durability properties when compared to that of all other mixes. The optimum replacement level of the discarded foundry sand by mass to the river sand was 40%. The lightweight concrete produced by utilizing crushed brick masonry aggregate and discarded foundry sand (40% substitution level) can be employed in all major structural lightweight construction aspects and is ideally suited for sloped roof slabs and making architectural or decorative concrete blocks.